Social Class Reflected In Characterization In Kevin Kwan’s China Rich Girlfriend - Kadek Ayu Dewi Prastika (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2020)
The aim of this study is to analyze the social class classification reflects on plot and characterization in China Rich Girlfriend novel. This study used Marxism approach to analyze social class classification reflects on this novel. The major principle of Marxism used in this novel is class struggle. The data analysis technique used was documentation. The researcher also used library research to find some relevant sources related to this study.This study showed that there are some major characters that explained how the lower-class and the upper-class had different style in using their money and also protect their wealth. Besides, it was found that there was a revolution appeared in this novel.